Polyamide-grafted polyolefin-containing thermoplastic resin composition

A thermoplastic resin composition combining polyamide-grafted polyolefin with polystyrene-polyisobutylene block copolymers and polyamide resin addresses the balance of extrusion processability, high-temperature strength, and moisture permeability in refrigerant transport hoses.

JP7602124B2Active Publication Date: 2024-12-18THE YOKOHAMA RUBBER CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021028911
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-25
Publication Date
2024-12-18
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

The existing resin composition for refrigerant transport hoses lacks sufficient moisture permeability resistance and does not have a balanced performance in extrusion processability, high-temperature strength, and flexibility.

Method used

A thermoplastic resin composition is formulated by blending polyamide-grafted polyolefin with a block copolymer containing polystyrene and polyisobutylene blocks, along with a polyamide resin, to achieve improved extrusion processability, high-temperature strength, and moisture permeation resistance.

Benefits of technology

The composition exhibits excellent balance of flexibility, high-temperature strength, and moisture permeability resistance, with specific properties such as maximum point stress, water vapor permeability, and melt viscosity within defined ranges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602124000001
    Figure 0007602124000001
  • Figure 0007602124000002
    Figure 0007602124000002
  • Figure 0007602124000003
    Figure 0007602124000003
Patent Text Reader

Abstract

To provide a thermoplastic resin composition which has good extrusion workability, and is excellent in balance between high temperature strength, moisture permeation resistance and flexibility.SOLUTION: A thermoplastic resin composition is provided, including 100 pts.mass of polyolefin (A) grafted with polyamide, 5-350 pts.mass of a polyamide resin (B), and 5-350 pts.mass of a block copolymer (C) including a polystyrene block and a polyisobutylene block. The thermoplastic resin composition has a maximum point stress in a tensile test at a temperature of 150°C and tensile speed of 500 mm / min of 1.0 MPa or more, and a coefficient of water vapor permeation at a temperature of 60°C and relative humidity of 100% of 13 cm3 mm / (m2 24h) or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamide-grafted polyolefin-containing thermoplastic resin composition. More specifically, the present invention relates to a thermoplastic resin composition comprising a polyolefin having a polyamide grafted thereon. [Background technology]

[0002] A resin composition containing a polyamide resin, a polyolefin elastomer, and a block copolymer having a structure in which a polyamide block is grafted onto a polyolefin skeleton is known as a resin composition used to form the innermost layer of a refrigerant transport hose that has excellent durability and barrier properties (JP 2019-23486 A). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-23486 A Summary of the Invention [Problem to be solved by the invention]

[0004] The resin composition described in JP 2019-23486 A does not have sufficient moisture permeability resistance. The present invention provides a thermoplastic resin composition which has good extrusion processability and an excellent balance of high-temperature strength, moisture resistance and flexibility. [Means for solving the problem]

[0005] The present inventors have discovered that by blending a polyamide-grafted polyolefin with a polyamide resin and a block copolymer containing a polystyrene block and a polyisobutylene block, a thermoplastic resin composition having good extrusion processability and an excellent balance of high-temperature strength, moisture resistance and flexibility can be obtained, and have completed the present invention. That is, the present invention relates to a thermoplastic resin composition comprising a polyamide-grafted polyolefin (A), a polyamide resin (B), and a block copolymer (C) containing a polystyrene block and a polyisobutylene block.

[0006] The present invention includes the following embodiments. [1] A thermoplastic resin composition comprising a polyamide-grafted polyolefin (A), a polyamide resin (B), and a block copolymer (C) containing a polystyrene block and a polyisobutylene block. [2] The thermoplastic resin composition according to [1], characterized in that the content of the block copolymer (C) containing a polystyrene block and a polyisobutylene block is 5 to 350 parts by mass based on 100 parts by mass of the polyamide-grafted polyolefin (A). [3] The thermoplastic resin composition according to [1] or [2], wherein the content of the polyamide resin (B) is 5 to 350 parts by mass based on 100 parts by mass of the polyamide-grafted polyolefin (A). [4] The thermoplastic resin composition according to any one of [1] to [3], characterized in that the maximum point stress in a tensile test conducted at a temperature of 150° C. and a tensile speed of 500 mm / min is 1.0 MPa or more. [5] The water vapor transmission coefficient at 60°C and 100% relative humidity is 13cm 3 mm / (m 2 The thermoplastic resin composition according to any one of [1] to [4], characterized in that the heating time is 24 hours or less. [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the polyamide resin (B) is at least one selected from the group consisting of polyamide 6, polyamide 66, polyamide 6 / 66 copolymer, polyamide 610, polyamide 6 / 12 copolymer, polyamide 11, polyamide 12, polyamide 1010 and polyamide 1012. [7] The thermoplastic resin composition according to any one of [1] to [6], which has a melt viscosity of 1000 Pa·s or less at a temperature of 250° C. and a shear rate of 243 / s. [8] The thermoplastic resin composition according to any one of [1] to [7], characterized in that the thermoplastic resin composition has a breaking elongation of 100% or more in a tensile test at a temperature of 25°C and a tensile speed of 500 mm / min after standing at 150°C for 168 hours in an air atmosphere. Effect of the Invention

[0007] The thermoplastic resin composition of the present invention has good extrusion processability and is excellent in balance of high-temperature strength, moisture resistance and flexibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention is a thermoplastic resin composition comprising a polyamide-grafted polyolefin (A), a polyamide resin (B), and a block copolymer (C) containing a polystyrene block and a polyisobutylene block.

[0009] The polyamide-grafted polyolefin (A) is a polymer in which a polyamide block is grafted to the backbone (main chain) of a polyolefin. The polyamide-grafted polyolefin is hereinafter also referred to as a "polyamide-grafted polyolefin." The polyamide-grafted polyolefin (A) can be obtained, for example, by mixing a polyolefin-based (co)polymer having a functional group with a polyamide having a reactive end group that reacts with the functional group in a molten state.

[0010] The polyolefin (hereinafter also referred to as "polyolefin main chain") that serves as the skeleton of the polyamide-grafted polyolefin (A) is not limited as long as it exerts the effects of the present invention, and examples thereof include homopolymers or copolymers of olefin monomers having 2 to 30 carbon atoms. Examples of the olefin monomer include α-olefins, cycloolefins, dienes, polyenes, and aromatic vinyl compounds. Examples of α-olefins include ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 1-docosene, 1-tetracosene, 1-hexacosene, 1-octacosene, and 1-triacontene, with ethylene and propylene being preferred. The cycloolefin is preferably a cycloolefin having 3 to 30 carbon atoms, more preferably a cycloolefin having 3 to 20 carbon atoms. Specific examples thereof include cyclopentane, cycloheptane, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene. Examples of dienes or polyenes include butadiene, isoprene, 4-methyl-1,3-pentadiene, 1,4-pentadiene, 1,5-hexadiene, 1,3-hexadiene, 1,3-octadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, ethylidenenorbornene, vinylnorbornene, dicyclopentadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, and 5,9-dimethyl-1,4,8-decatriene. Examples of aromatic vinyl compounds include mono- or polyalkylstyrenes (styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, etc.), methoxystyrene, ethoxystyrene, vinylbenzoic acid, vinyl methylbenzoate, vinylbenzyl acetate, hydroxystyrene, o-chlorostyrene, p-chlorostyrene, divinylbenzene, 3-phenylpropene, 4-phenylpropene, α-methylstyrene, etc.

[0011] The polyolefin backbone contains the residue of an unsaturated comonomer having a functional group capable of reacting with the reactive end group of the polyamide block, such as an unsaturated epoxide, an unsaturated carboxylic acid or salt thereof, a carboxylic acid anhydride, or the like. Examples of the unsaturated epoxide include aliphatic glycidyl ethers such as allyl glycidyl ether and vinyl glycidyl ether; aliphatic glycidyl esters such as glycidyl maleate, glycidyl itaconate, glycidyl acrylate, and glycidyl methacrylate; alicyclic glycidyl ethers such as 2-cyclohexene-1-glycidyl ether; and alicyclic glycidyl esters such as glycidyl cyclohexene-4,5-dicarboxylate, glycidyl cyclohexene-4-carboxylate, glycidyl 5-norbornene-2-methyl-2-carboxylate, and diglycidyl endo-cis-bicyclo[2.2.1]-5-heptane-2,3-dicarboxylate, with glycidyl methacrylate being preferred. The unsaturated carboxylic acid or its salt includes acrylic acid, methacrylic acid, and the like, and their salts. Examples of the carboxylic acid anhydride include maleic anhydride, itaconic anhydride, citraconic anhydride, allylsuccinic anhydride, cyclohex-4-ene-1,2-dicarboxylic anhydride, 4-methylenecyclohex-4-ene-1,2-dicarboxylic anhydride, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, and methylbicyclo[2.2.1]hept-5-ene-2,2-dicarboxylic anhydride, and preferably maleic anhydride.

[0012] The polyamide constituting the polyamide block of the polyamide-grafted polyolefin (A) is not limited as long as it exerts the effects of the present invention, but examples thereof include polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 66, polyamide 69, polyamide 610, polyamide 612, polyamide 1012, polyamide 1212, polyamide PACM12, polyamide BMACM10, polyamide BMACM12, polyamide 6T, polyamide 6I, polyamide MXD6, polyamide MXD10, polyamide 66 / 6T copolymer, polyamide 6 / 66 copolymer, and the like, with polyamide 6 being preferred.

[0013] The polyamide block has a residue of a reactive end group that reacts with the functional group of the polyolefin (co)polymer. The reactive end group is an amino group or a carboxyl group. The polyamide having a reactive end group preferably has only one reactive end group. That is, the polyamide having a reactive end group is preferably monofunctional. To make the polyamide having a reactive end group monofunctional, the terminal amino group of the polyamide is capped with a carboxylic acid, a carboxylic anhydride or a dicarboxylic acid, or the terminal carboxyl group of the polyamide is capped with an amine such as laurylamine or oleylamine.

[0014] Polyamide-grafted polyolefin (A) is commercially available, and a commercially available product can be used in the present invention. An example of a commercially available product of polyamide-grafted polyolefin (A) is APOLHYA (registered trademark) manufactured by Arkema.

[0015] The polyamide resin (B) is not limited as long as it exerts the effects of the present invention, but is preferably at least one selected from the group consisting of polyamide 6, polyamide 66, polyamide 6 / 66 copolymer, polyamide 610, polyamide 6 / 12 copolymer, polyamide 11, polyamide 12, polyamide 1010 and polyamide 1012.

[0016] The block copolymer (C) containing a polystyrene block and a polyisobutylene block is not limited as long as it exhibits the effects of the present invention, and may be a styrene-isobutylene-styrene block copolymer (SIBS) or a styrene-isobutylene block copolymer (SIB), preferably a styrene-isobutylene-styrene block copolymer (SIBS). The block copolymer containing a polystyrene block and a polyisobutylene block is hereinafter also referred to simply as "block copolymer (C)".

[0017] The content of the polyamide resin (B) in the thermoplastic resin composition is preferably 5 to 350 parts by mass, more preferably 10 to 200 parts by mass, and even more preferably 20 to 150 parts by mass, based on 100 parts by mass of the polyamide-grafted polyolefin (A). If the content of the polyamide resin (B) is too small, the high-temperature strength may be insufficient. If the content of the polyamide resin (B) is too large, the flexibility may be insufficient.

[0018] The content of the block copolymer (C) in the thermoplastic resin composition is preferably 5 to 350 parts by mass, more preferably 10 to 250 parts by mass, and even more preferably 20 to 200 parts by mass, based on 100 parts by mass of the polyamide-grafted polyolefin (A). If the content of the block copolymer (C) is too low, there is a risk of insufficient moisture permeation resistance. If the content of the block copolymer (C) is too high, there is a risk of insufficient high-temperature strength.

[0019] The maximum point stress in a tensile test of the thermoplastic resin composition at a temperature of 150°C and a tensile speed of 500mm / min is preferably 1.0MPa or more, more preferably 1.2 to 20MPa, and even more preferably 1.4 to 15MPa. The maximum point stress in a tensile test at a temperature of 150°C and a tensile speed of 500mm / min is hereinafter also referred to as "maximum point stress at 150°C". If the maximum point stress at 150°C is too low, the high temperature strength is poor. Methods for making the maximum point stress at 150°C fall within the above numerical range include adjusting the content ratio of the polyamide grafted polyolefin (A), the polyamide resin (B), and the block copolymer (C), selecting the polyamide block and the polyamide resin (B) in the polyamide grafted polyolefin (A), and adding a filler.

[0020] The thermoplastic resin composition preferably has a water vapor permeability coefficient of 13 cm at a temperature of 60° C. and a relative humidity of 100%. 3 mm / (m 2 24h or less, and more preferably 0.1 to 11cm 3 mm / (m 2 24h), and more preferably 0.5 to 9 cm 3 mm / (m 2 If the water vapor permeability coefficient is too high, the moisture permeability resistance is poor. Methods for making the water vapor permeability coefficient fall within the above numerical range include adjusting the content ratio of polyamide grafted polyolefin (A), polyamide resin (B) and block copolymer (C), and selecting the polyamide block and polyamide resin (B) in polyamide grafted polyolefin (A).

[0021] The melt viscosity of the thermoplastic resin composition at a temperature of 250°C and a shear rate of 243 / s is preferably 1000 Pa·s or less, more preferably 30 to 950 Pa·s, and even more preferably 50 to 900 Pa·s. If the melt viscosity is too high, the extrusion processability is poor. Methods for making the melt viscosity fall within the above numerical range include selecting the molecular weights of the polyamide-grafted polyolefin (A), the polyamide resin (B), and the block copolymer (C), and adding processing tablets such as plasticizers and metal soaps.

[0022] The breaking elongation of the thermoplastic resin composition in a tensile test at 25°C and a tensile speed of 500mm / min after standing at 150°C for 168 hours in an air atmosphere is preferably 100% or more, more preferably 130-1000%, and even more preferably 160-800%. The breaking elongation in a tensile test at 25°C and a tensile speed of 500mm / min after standing at 150°C for 168 hours in an air atmosphere is hereinafter also referred to as "breaking elongation after heat aging". If the breaking elongation after heat aging is too low, the flexibility is poor. Methods for making the breaking elongation after heat aging fall within the above numerical range include adjusting the content ratio of the polyamide grafted polyolefin (A), the polyamide resin (B), and the block copolymer (C), and adding a heat resistant anti-aging agent.

[0023] The method for producing the thermoplastic resin composition is not limited as long as the effects of the present invention are achieved, but for example, the thermoplastic resin composition can be produced by melt-kneading the polyamide-grafted polyolefin (A), the polyamide resin (B), and the block copolymer (C). The melt-kneading can be carried out, for example, using a twin-screw kneading extruder with the cylinder temperature set to a temperature 15 to 25°C higher than the melting point of the polymer with the highest melting point, under the condition of a residence time of 4 to 6 minutes.

[0024] INDUSTRIAL APPLICABILITY The thermoplastic resin composition of the present invention can be used as a material for hoses which require high-temperature strength and moisture permeability resistance, and can be particularly suitably used as a material for making the inner layer or outer layer of an air conditioner hose. EXAMPLES

[0025] (1) Raw materials The raw materials used in the following examples and comparative examples are as follows.

[0026] [Polyamide grafted polyolefin (A)] APOLHYA (registered trademark) LP21H: Manufactured by Arkema, polyolefin grafted with polyamide 6 (Young's modulus: 100 MPa) APOLHYA (registered trademark) LP2: Manufactured by Arkema, polyolefin grafted with polyamide 6 (Young's modulus: 65 MPa) APOLHYA (registered trademark) LP3: Manufactured by Arkema, polyolefin grafted with polyamide 6 (Young's modulus: 30 MPa)

[0027] [Polyamide resin (B)] PA6: Polyamide 6 "UBE Nylon" (registered trademark) 1013B manufactured by Ube Industries, Ltd. PA6 / 66: Polyamide 6 / 66 copolymer "UBE Nylon" (registered trademark) 5023B manufactured by Ube Industries, Ltd. PA6 / 12: Polyamide 6 / 12 copolymer "UBE Nylon" (registered trademark) 7023B manufactured by Ube Industries, Ltd. PA610: Polyamide 610 "Amilan" (registered trademark) CM2001 manufactured by Toray Industries, Inc. PA1010: Polyamide 1010 "Vestamid" (registered trademark) DS16 manufactured by Daicel-Evonik Co., Ltd.

[0028] [Block copolymer (C) containing polystyrene blocks and polyisobutylene blocks] SIBS-1: Kaneka Corporation styrene-isobutylene-styrene block copolymer "SIBSTAR" (registered trademark) 102T (hardness: A25, breaking strength (JIS K6251, dumbbell-shaped No. 3, 23°C): 15MPa) SIBS-2: Kaneka Corporation styrene-isobutylene-styrene block copolymer "SIBSTAR" (registered trademark) 103T (hardness: A46, breaking strength: 18MPa) SIBS-3: Kaneka Corporation styrene-isobutylene-styrene block copolymer "SIBSTAR" (registered trademark) 072T (hardness: A33, breaking strength: 13MPa)

[0029] [Elastomer that does not contain polystyrene blocks or polyisobutylene blocks] Mah-EB: Maleic anhydride modified ethylene-1-butene copolymer "Tafmer" (registered trademark) MH7010 manufactured by Mitsui Chemicals, Inc. Br-IPMS: Brominated isobutylene-p-methylstyrene copolymer "EXXPRO" (registered trademark) 3745 manufactured by ExxonMobil Chemical Corporation

[0030] (2) Preparation of Thermoplastic Resin Composition The polyamide-grafted polyolefin (A), polyamide resin (B), block copolymer (C) or other elastomer was introduced into a twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd.) with the cylinder temperature set to the melting point of the polymer with the highest melting point + 20°C in the formulation shown in Tables 1 to 3, melt-kneaded for a residence time of about 5 minutes, and the molten kneaded product was extruded in a strand shape from a die attached to the discharge port. The obtained strand-shaped extrudate was pelletized with a resin pelletizer to obtain a pellet-shaped thermoplastic resin composition.

[0031] (3) Evaluation of thermoplastic resin composition The thermoplastic resin composition prepared in (2) above was evaluated for extrusion processability, maximum point stress at 150°C, water vapor permeability coefficient, melt viscosity, and breaking elongation after heat aging. The evaluation results are shown in Tables 1 to 3. The evaluation methods for each evaluation item are as follows.

[0032] (4) Preparation of Thermoplastic Resin Composition Sheets for Evaluation The pellet-shaped thermoplastic resin composition prepared in (2) above was molded into a sheet having an average thickness of 0.2 mm using a 40 mmφ single-screw extruder equipped with a 200 mm wide T-type die (Pla Giken Co., Ltd.) with the cylinder and die temperatures set to the melting point of the polymer with the highest melting point in the thermoplastic resin composition + 20°C, a cooling roll temperature of 50°C, and a take-up speed of 3 m / min.

[0033] (5) Evaluation of extrusion processability When the sheet was melt-extruded in the above (4), a 100 cm length of the sheet was cut out in the extrusion direction 30 minutes after the start of extrusion, and the thickness variations in the extrusion direction and width direction were measured and expressed as an index with the thickness variation in Comparative Example 1 set to 100. When the index was less than 95, the thickness variation was smaller than that of Comparative Example 1, and the extrusion processability was excellent, and the result was judged to be "excellent." When the index was 95 or more and less than 105, the extrusion processability was equivalent to that of Comparative Example 1 and was judged to be "good." When the index was 105 or more and 115 or less, the thickness variation was larger than in Comparative Example 1, but was at a level that did not pose a problem in use, and was judged to be "passable." If the index exceeds 115, there is a large variation in thickness, which may cause problems in use, and it is judged as "unacceptable."

[0034] (6) Measurement of maximum point stress at 150℃ The sheet of the thermoplastic resin composition prepared in (4) above was punched out into a JIS No. 3 dumbbell shape, and a tensile test was carried out at a temperature of 150°C and a tensile speed of 500 mm / min in accordance with JIS K6301 "Physical Testing Methods for Vulcanized Rubber". The maximum point stress (MPa) was obtained from the obtained stress-strain curve. The maximum point stress at 150°C is a measure of high-temperature strength, and a larger maximum point stress at 150°C means a higher high-temperature strength.

[0035] (7) Measurement of water vapor permeability coefficient A sheet of the thermoplastic resin composition prepared in (4) above was cut out and measured for water vapor permeability coefficient (cm) at a temperature of 60°C and a relative humidity of 100% using a water vapor permeability tester manufactured by GTR Tech Co., Ltd. 3 mm / (m 2 -24h) was measured.

[0036] (8) Measurement of melt viscosity The pellet-shaped thermoplastic resin composition prepared in (2) above was dried at 80°C for 8 hours, and then the melt viscosity (Pa s) was measured by detecting the load using a capillary rheometer at a temperature of 250°C, a piston speed of 5 mm / min, a capillary length of 10 mm, and a capillary inner diameter of 1 mm (i.e., a shear rate of 243 / s).

[0037] (9) Measurement of breaking elongation after heat aging The sheet of the thermoplastic resin composition prepared in (4) above was left to stand in an oven set at 150°C in an air atmosphere for 168 hours to carry out a heat aging treatment. The sheet after the heat aging treatment was punched into a JIS No. 3 dumbbell shape and a tensile test was carried out at a temperature of 25°C and a tensile speed of 500 mm / min in accordance with JIS K6301 "Physical test method for vulcanized rubber". The breaking elongation (%) was obtained from the obtained stress-strain curve.

[0038] [Table 1]

[0039] [Table 2]

[0040] [Table 3] [Industrial Applicability]

[0041] The thermoplastic resin composition of the present invention can be suitably used as a material for hoses, which require high-temperature strength and moisture resistance.

Claims

1. A thermoplastic resin composition comprising a polyamide-grafted polyolefin (A), a polyamide resin (B), and a block copolymer (C) containing a polystyrene block and a polyisobutylene block, wherein the content of the polyamide resin (B) is 5 to 350 parts by mass based on 100 parts by mass of the polyamide-grafted polyolefin (A), and the content of the block copolymer (C) containing a polystyrene block and a polyisobutylene block is 5 to 350 parts by mass based on 100 parts by mass of the polyamide-grafted polyolefin (A).

2. 2. The thermoplastic resin composition according to claim 1, which has a maximum stress of 1.0 MPa or more in a tensile test at a temperature of 150° C. and a tensile speed of 500 mm / min.

3. The water vapor transmission coefficient at a temperature of 60°C and a relative humidity of 100% is 13 cm 3 mm / (m 2 The thermoplastic resin composition according to claim 1 or 2, characterized in that the hardness is 24 h or less.

4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein the polyamide resin (B) is at least one selected from the group consisting of polyamide 6, polyamide 66, polyamide 6 / 66 copolymer, polyamide 610, polyamide 6 / 12 copolymer, polyamide 11, polyamide 12, polyamide 1010 and polyamide 1012.

5. 5. The thermoplastic resin composition according to claim 1, which has a melt viscosity of 1000 Pa·s or less at a temperature of 250° C. and a shear rate of 243 / s.

6. The thermoplastic resin composition according to any one of claims 1 to 5, characterized in that the thermoplastic resin composition has a breaking elongation of 100% or more in a tensile test at a temperature of 25°C and a tensile speed of 500 mm / min after being left to stand at 150°C for 168 hours in an air atmosphere.

Citation Information

Patent Citations

  • Refrigerant transport hose

    JP1990022050A

  • Thermoplastic elastomer composition and molded article

    JP2017105973A

  • Refrigerant transport hose

    JP2019023486A

  • Refrigerant transport hose

    JP2019023487A

  • Thermoplastic elastomer composition and molded article

    JP2019099602A